YADI NAASTI DAIVAM- A PRINCIPLE OF PREVIOUS LIFE’S DEEDS - Arora, Nishi; Shrivastava, Nidhi (International Journal of Research -GRANTHAALAYAH, 2018)
It is commonly observed all throughout history, felt all throughout our lives, that often, the achievements gained by people are not really tantamount to the amount of effort they have put in to try to achieve the same. This raises doubts on the saying ‘Hard work is the key to success’ as some people don’t work hard at all but achieve greater than those who have bet their lives on the same goal. To these conflicts that arise in our minds, causing depression and anxiety symptoms in some people can all be answered by a quarter of a verse found in the ancient text of Ayurveda, Charak Samhita. It also provides reasoning and solutions about the daily conflicts in society to some extent. Six principles were extracted from the same quarter of the verse by the author. It was concluded that people should: remain in present time and perform duties with utmost of precaution, not get discouraged by failures as they do not always imply that their present actions are incorrect, keep in mind that what they get is due to the balance of duties that they have performed, remember that whether the duties were performed in present or past, no one else is responsible for anyone else’s agony or pleasure.